Clinical and electrophysiological evaluation of dysphagia in myasthenia gravis - Ertekin, C. (BMJ Group, 1998)
OBJECTIVE—To evaluate dysphagia at the oropharyngeal stage of swallowing and to determine the pathophysiological mechanisms of dysphagia in patients with myasthenia gravis. METHODS—Fifteen patients with myasthenia gravis with dysphagia and 10 patients without dysphagia were investigated by a combined electrophysiological and mechanical method described previously. Laryngeal movements were detected by a piezoelectric transducer and the related submental EMG (SM-EMG) and sometimes the EMG of cricopharyngeal muscle of the upper esophageal sphincter (CP-EMG) were recorded during dry or wet swallowing. The results of these electrophysiological variables were compared with those of normal age matched control subjects. RESULTS—In patients with myasthenia gravis with dysphagia, it was found that the time necessary for the larynx to remain in its superior position during swallowing and swallowing variability in successive swallows increased significantly compared with normal subjects and with patients with myasthenia gravis without dysphagia. The total duration of SM-EMG activity was also prolonged in both groups but more severely in the dysphagic patients. Electromyographic activity of the CP sphincter was found to be normal in the dysphagic patients investigated. All the patients with myasthenia gravis with dysphagia had pathological dysphagia limits (<20 ml water) whereas other patients except two, were within normal limits. CONCLUSIONS—Because the electrophysiological variables related to oropharyngeal swallowing were prolonged even in patients with myasthenia gravis without dysphagia, it is concluded that the submental and laryngeal elevators are involved subclinically in myasthenia gravis and, because of compensating mechanisms, the patient may not be dysphagic. As the CP-EMG behaviour was found to be normal, a coordination disorder between normal CP sphincter muscle and the affected striated muscles of the laryngeal elevators may be one of the reasons for dysphagia in myasthenia gravis. This method also made it possible to investigate the myasthenic involvement in the laryngeal elevators that cannot be evaluated by other electrophysiological methods in myasthenia gravis.